On Ramsey (C4, K1, n)-minimal graphs - Hilda Assiyatun; Maya Nabila; Edy Tri Baskoro (Electronic Journal of Graph Theory and Applications (EJGTA), 2023)
Let F, G and H be any simple graphs. The notation F → (G, H) means for any red-blue coloring on the edges of graph F, there exists either a red copy of G or a blue copy of H. If F → (G, H), then graph F is called a Ramsey graph for (G, H). Additionally, if the graph F satisfies that F − e ↛ (G, H) for any edge e of F, then graph F is called a Ramsey (G, H)-minimal. The set of all Ramsey (G, H)-minimal graphs is denoted by ℛ(G, H). In this paper, we construct a new class of Ramsey (C4, K1, n)-minimal graphs.